Criticism of Hadiths on Earning a Livelihood: Compilation of Hadiths from the book “Islah al-Hal bi Thalab al-Halal” by Habib Utsman al-Batawi - Nurhakim, Amien; Fatihunnada, Fatihunnada (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2023)
Hadith has an essential role in the ethical guidelines for seeking halal sustenance. This article aims to trace the validity and quality of the hadith in Sayyid Utsman al-Batawi's work entitled